Who wrote that song? - Jacobs, Dick (Betterway Publ., 1988)
Includes lists of award-winning songs and of the inductees to the National Academy of Popular Music Songwriters' Hall of Fame.
Keywords: Popular music -- United States -- Bibliography; Schlager; USA; Bibliografie; Verzeichnis